Additively Manufactured Absorbable Porous Metal Implants – Processing, Alloying and Corrosion Behavior - Jahr, Holger; Li, Yageng; Zhou, Jie; Zadpoor, Amir A.; Schröder, Kai-Uwe (Frontiers in Materials, 2021)
Treating large bone defects is still a clinical challenge without perfect solution, mainly due to the unavailability of suitable bone implants. Additively manufactured (AM) absorbable porous metals, on the other hand, provide unparalleled opportunities to realize the challenging requirements for bone-mimetic implants. Firstly, multi-scale geometries of such implants can be customized to mimic the micro-architecture and mechanical properties of human bone. Additionally, interconnected porous structures possess larger surface areas to facilitate adhesion and proliferation of bone cells. Finally, their absorption properties are tunable to maintain the structural integrity of the implant throughout the bone healing process, ensuring sufficient loadbearing when needed and full disintegration after their job is done. Such a combination of properties paves the way for complete bone regeneration and remodeling. To develop such an ideal porous absorbable metal implant, it is important to thoroughly characterize its biocompatibility, biodegradation behavior, mechanical properties, and bone regeneration ability. We will review the state-of-the-art of absorbable porous metals manufactured by selective laser melting (SLM), with a focus on geometrical design, material type, processing, and post-treatment. The impact of the latter aspects on cytocompatibility, absorption behavior, and the resulting mechanical properties will also be briefly discussed. In comparison to their solid counterparts, AM absorbable porous metals have shown many unique properties and hold tremendous potential to further optimize their application-specific performance due to the flexibility of their geometrical design. This paper further aims at presenting current knowledge gaps and challenges encountered in adopting AM absorbable porous metals for future orthopedic solutions.